A novel convergent–divergent annular nozzle design for close-coupled atomisation. (27th May 2017) - Schwenck, Daniel; Ellendt, Nils; Fischer-Bühner, Jörg; Hofmann, Peter; Uhlenwinkel, Volker
ABSTRACT: Additive manufacturing processes such as selective laser melting and electron beam melting require small particle sizes. A widely used technique to produce suitable powders is close-coupled atomisation. To further decrease the achieved particle sizes, the annular geometry of the gas nozzle is changed to a convergent–divergent (CD) profile. This novel configuration is capable of operating stably at low pressures of 0.8 MPa and above. Beyond that, the unwanted effects of lick-back are avoided. Different nozzles with conventional and convergent–divergent annular geometry have been designed based on fluid-flow calculations. The aspiration pressure was measured to determine stable process windows. Powders from a CuSn alloy were produced using cold and hot gas atomisation to show the influence on the process stability, particle size and morphology. High-speed recordings are used to investigate the process conditions of the different nozzle configurations.